CHANGES IN THE CONTENT OF AMINO ACIDS AND ALDEHYDES DURING THE THERMAL TREATMENT OF VINOMATERIALS FOR LIQUEUR WINES - V. E. Strukova; M. A. Nazarenko; L. I. Stribizheva (Современная наука и инновации, 2022)
One of the main factors in the process of typing (port wine) wines is heat treatment, which is accompanied by the reaction of melanoidin formation. The study and understanding of these processes facilitates the possibility of regulating the reaction towards the formation of characteristic compounds for a particular type of wine. Most of the nitrogenous substances in wines are amino acids. They are involved in the darkening reactions of liqueur wines, are sources of formation of substances such as aldehydes, higher alcohols, which affects the organoleptic characteristics of wines.